2019
DOI: 10.21273/hortsci14168-19
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Morphological and Biochemical Properties in Organically Grown Zucchini Squash (Cucurbita pepo L.)

Abstract: The present research was undertaken with the aim of justifying the effect of morphological, physiological, and nutritional properties in organically produced zucchini squash. The experiment consisted of two factors: three levels of pruning (P0 = no pruning, P1 = primary pruning at 20 days after transplanting (DAT), and P2 = secondary pruning at 30 DAT) and four levels of vermicompost application (V0 = control, V Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
1
0
1
Order By: Relevance
“…Individual fruit weight has significant and positive correlation with fruit/plant (0.93*), fruit length (0.92*), and fruit diameter (0.88*). The findings are in agreement with the findings of (Uddain et al, 2019). The yield of squash was positively correlated with fruit length, fruit diameter, fruit/plant and Individual fruit weight.…”
Section: Correlation Studysupporting
confidence: 92%
“…Individual fruit weight has significant and positive correlation with fruit/plant (0.93*), fruit length (0.92*), and fruit diameter (0.88*). The findings are in agreement with the findings of (Uddain et al, 2019). The yield of squash was positively correlated with fruit length, fruit diameter, fruit/plant and Individual fruit weight.…”
Section: Correlation Studysupporting
confidence: 92%
“…No significant interactions between the effect of the cultivar and horticultural system on the sugars content in the tested fruits were observed. Compared to the presented results, higher average sugars content was reported by other authors in the fruits of Cucurbita maxima [42], Cucurbita pepo [44,45], and Cucurbita moschata D. [46]. Other studies reported that courgette fruits also contain galactose, raffinose, stachyose, and starch.…”
Section: Dry Matter and Sugars In Courgette Fruitscontrasting
confidence: 85%